The Influence of Synsedimentary Faults on the Restoration of the Original Basin - Ren, Jiawei (Scientific Journal of Technology, 2026)
The restoration of the original basin is a core geological task for reconstructing the original appearance of sedimentary basins, revealing the evolution laws of basins, and guiding the exploration of oil, gas and other mineral resources. As a tectonic phenomenon that occurs simultaneously with sedimentation during the evolution of sedimentary basins, syn-sedimentary faults directly control the boundary morphology of the basin, the migration of sedimentary centers, the distribution of strata thickness and the paleogeomorphic features. They are key controlling factors that cannot be ignored in the process of original basin restoration. This paper systematically reviews the relevant research results of syn-sedimentary faults and original basin restoration, elaborates on the geological overview of typical regions, summarizes the current research status at home and abroad and the commonly used research methods, and focuses on discussing the classification of syn-sedimentary faults, the methods of paleogeomorphic restoration under the control of syn-sedimentary faults, as well as the specific impacts of syn-sedimentary faults on the boundaries of the original basin, sedimentary filling and tectonic patterns. Finally, it summarizes the existing deficiencies in current research and looks forward to future research directions, providing theoretical references and technical support for subsequent original basin restoration research and mineral resource exploration.